Bora phosphorylation substitutes in trans for T-loop phosphorylation in Aurora A to promote mitotic entry - N. Tavernier (Nature Portfolio, 2021)
Tavernier et al. decipher the mechanism by which the intrinsically disordered protein Bora, phosphorylated by Cyclin-Cdk, potentiates AURKA activity towards Polo-like kinase 1. Furthermore, they demonstrate the importance of this mechanism for timely mitotic entry in Xenopus and human cells.